185 - EDUCATION PERMANENT EMPLOYEES OF NURSING FOR THE TREATMENT OF WOUNDS IN THE CITY OF SANTANA DO MATOS / RN (Fiep Bulletin - online, 2011)
Exploratory-descriptive study, whose objectives are to identify prior knowledge of nursing professionals about the treatment of wounds, the material resources that the nursing staff used / available to accomplish this treatment, possible difficulties in carrying out this activity and ultimately the effectiveness continuing education in wound care. The sample consisted of 33 nurses who are in care. The results showed higher frequency of females (93.9%), age range: 40 to 49 (42.4%) and the Joint Unit and sector work (66.7%). The majority of respondents (51.5%) passed the course / training on the subject and 57.6% felt prepared to make a dressing. The products most remembered are 0.9% saline, gauze, adhesive tape and bandage (100.0%). The results of the second part of the research showed that on the healing process 52.4% of respondents missed the answers. When asked about venous ulcer (pre-test: 71.5% and post-test 95.8%) respondents agreed most of the answers, the same happened with respect to arterial ulcers (pre-test: 60.3% and post-test: 96.1%), diabetes (pre-test: 77.6%% and post-test: 95.2%) and pressure (pre-test: 69.7% and post-test: 90, 3%). Already on the technique of dressing and use of covers, it was observed that respondents had some errors (19.7%), these being reduced after training (2.4%). The completion of continuing education can change the knowledge of professionals on the treatment of wounds, provided it is done constantly contributing to the information and discussing the technical and interpersonal development to promote quality care and humane.
Keywords: continuing education; wounds; nursing